MT-MMPS as Regulators of Vessel Stability Associated with Angiogenesis - Sounni, Nor Eddine; Paye, Alexandra; Host, Lorin; Noël, Agnès (Frontiers in Pharmacology, 2011)
The development of vascular system depends on the coordinated activity of a number of distinct families of molecules including growth factors and their receptors, cell adhesion molecules, extracellular matrix (ECM) molecules and proteolytic enzymes. Matrix metalloproteases (MMPs) are a family of ECM degrading enzymes required for both physiological and pathological angiogenesis. Increasing evidence, point to a direct role of membrane type-MMPs (MT-MMPs) in vascular system stabilization, maturation and leakage. Our understanding of the nature of MT-MMP interaction with extracellular and cell surface molecules and their multiple roles in vessel walls and perivascular stroma may provide new insights into mechanisms underlying vascular cell-ECM interactions and cell fate decisions in pathological conditions. Regulation of vascular leakage by MT-MMP interactions with the ECM could also lead to novel targeting opportunities for drug delivery in tumor. This review will shed lights on the emerging roles of MT1-MMP and MT4-MMP in vascular system alterations associated with cancer progression.